IoT Pet Feeder / Ahmad Akif Farhan Mohd Yuzi and Muhammad Fathullah Hakim Jaafar - Mohd Yuzi, Ahmad Akif Farhan; Jaafar, Muhammad Fathullah Hakim (2022)
Internet of Things (IoT) Pet Feeder is an automatic feeding machine designated for pets by using applications inside the phone device called Blynk apps. Feeding a pet is one of the priority for the owners as they were going through their daily routine. Unfortunately, the busyness and limited of time at work causes lacking of care and owner almost forgot to feed their pets. In addition, the machine is fabricated and designated to work easily, equipped with an advanced technology which is innovated with the addition of an internet connection between the mobile device and WiFi Module. It will give an advantage for the owner because the machine can work automatically, so it will allow efficient feeding process and save owner’s time and energy to feed their pets. Furthermore, most of the pet feeder system are still using the conventional method. With IoT application, it is an effective way to enhance the productivity of feeding process and utilize top and local users, especially in the mechanical industry.